Pengembangan Kapasitas Usaha Kecil Kerupuk Kentang Di Kampung Ciawitali Desa Warnasari Kecamatan Pangalengan Kabupaten Bandung - Erlangga, Heri; Abdurohim, Dindin; Yuniarti, Yuyun; Dinihayati, Erti (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2020)
This potato cracker business is located in Ciawitali Village, Warnasari Village RT / RW 01/08, Pangalengan District. Regency. Bandung - West Java is located in the southern part of Bandung Regency, which is 51 kilometers from the center of Bandung City and 23 kilometers from the capital city of Bandung Regency, namely Soreang, Pangalengan District is one of the tourism icons of Bandung Regency and still has a number of hidden potentials. This potential must still be explored and developed for the welfare of society. Some of them are culinary potentials that have not been widely known so far. Another potential that can still be explored is potato crackers, where potatoes are a superior agricultural commodity from Pangalengan. Warnasari Village is part of Pangalengan District, Bandung Regency, West Java Province. Likewise, in Warnasari Village there is still potential, where there are some people who depend on their livelihoods by exploiting the potential of several sectors of agriculture, plantations, services and others through entrepreneurship (business actors / MSMEs). Problems in general are related to business managerial, including production, human resources, finance and marketing. Priority problems for partners, namely the low motivation of partners to develop their businesses and unstructured business management, especially marketing and business development that have not yet developed. The solution offered: Implementation of entrepreneurial motivation training and business management and product marketing.